2022
DOI: 10.1002/advs.202205054
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneously Constructing Active Sites and Regulating Mn–O Strength of Ru‐Substituted Perovskite for Efficient Oxidation and Hydrolysis Oxidation of Chlorobenzene

Abstract: Chlorinated volatile organic compounds (CVOCs) are a class of hazardous pollutants that severely threaten environmental safety and human health. Although the catalytic oxidation technique for CVOCs elimination is effective, enhancing the catalytic efficiency and simultaneously inhibiting the production of organic byproducts is still of great challenge. Herein, Ru‐substituted LaMn(Ru)O 3+ δ perovskite with Ru–O–Mn structure and weakened Mn–O bond strength has been dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…This observation is further supported by the lowest force constant ( k ) value for Mn–O bonds in Pd/Mn 3 O 4 –MnO-1 (Figures S21 and S22). The weaker Mn–O bond results in increased oxygen vacancy ( O v ) formation, which is consistent with the findings from EPR tests (Figure S23). The presence of O v typically enhances both the mobility and reactivity of oxygen …”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This observation is further supported by the lowest force constant ( k ) value for Mn–O bonds in Pd/Mn 3 O 4 –MnO-1 (Figures S21 and S22). The weaker Mn–O bond results in increased oxygen vacancy ( O v ) formation, which is consistent with the findings from EPR tests (Figure S23). The presence of O v typically enhances both the mobility and reactivity of oxygen …”
Section: Resultssupporting
confidence: 89%
“…Surface oxygen was characterized by XPS. The O 1s spectra (Figure b) are deconvoluted into three distinct peaks, corresponding to the lattice oxygen ( O latt ), surface-adsorbed oxygen ( O ads ), and physi/chemisorbed water ( O OH ), respectively. , Generally, O ads exhibits high electron density and is more prone to react with organic molecules, displaying enhanced activity in the oxidation of VOCs . However, no significant difference is observed in the proportions of O ads on Pd/Mn 3 O 4 –MnO-1, Pd/MnO, and Pd/Mn 3 O 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Magnetite (Fe 3 O 4 ) is an earth-abundant TM oxide with an inverse spinel structure (Fe A 3+ (Fe 2+ Fe 3+ ) B O 4 ), in which electrons quickly transfer between Fe 2+ and Fe 3+ on the octahedral sites (B sites), endowing it a potential catalyst with good electrical conductivity. , However, this iron oxide exhibits low activity toward VOCs oxidation owing to its insufficient low-temperature reducibility and surface oxygen species . Numerous studies have demonstrated that regulating the metal–oxygen bond strength can boost the catalytic performance by enhancing the reactivity of surface lattice oxygen (O latt ), which is crucial for VOCs degradation based on the Mars-van Krevelen (MvK) mechanism. For example, Zhang et al discovered that the oxidation activity of toluene could be improved by engineering the Co–O bond strength in Co 3 O 4 catalysts due to the increased amount of reactive oxygen species .…”
Section: Introductionmentioning
confidence: 99%
“…For example, the strength of the Mn 3+ –O bond was weakened owing to the formation of Cu 2+ –O–Mn 4+ , which boosted the redox and oxygen activation capabilities of the catalysts . The fabrication of the Ru–O–Mn structure over Ru-substituted perovskite creates active sites and regulates the Mn–O strength simultaneously, thereby exhibiting excellent catalytic activity for chlorobenzene conversion . Moreover, the Cu–O–Ti hybridization structure in the Cu 1 /TiO 2 catalyst promoted the adsorption and activation of molecular O 2 and triggered lattice distortion for activating surface O latt …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation